Expert Review on Contemporary Management of Common Benign Pleural Effusions - Porcel, José M. (Seminars in Respiratory and Critical Care Medicine, 2023)
Heart failure (HF) and cirrhosis are frequently associated with pleural effusions (PEs). Despite their apparently benign nature, both HF-related effusions and hepatic hydrothorax (HH) have poor prognosis because they represent an advanced stage of the disease. Optimization of medical therapy in these two entities involve not only the use of diuretics, but also other pharmacological therapies. For instance, all HF patients with reduced or mildly reduced left ventricular ejection fraction can benefit from angiotensin receptor–neprilysin inhibitors, beta blockers, mineralocorticoid receptor antagonists, and sodium-glucose cotransporter 2 inhibitors. Conversely, it is better for HH patients to avoid nonselective beta blockers. Refractory cardiac- and cirrhosis-related PEs are commonly managed by iterative therapeutic thoracentesis. When repeated aspirations are needed, thereby diminishing quality of life, the insertion of an indwelling pleural catheter (IPC) may be warranted. However, in selected HH patients who are diuretic-resistant or diuretic-intractable, placement of transjugular intrahepatic portosystemic shunts should be considered as a bridge to liver transplantation, whereas in transplant candidates the role of IPC is debatable. Another benign condition, pleural tuberculosis (TB) is a serious health problem in developing countries. Diagnostic certainty is still a concern due to the paucibacillary nature of the infection, although the use of more sensitive nucleic acid amplification tests is becoming more widespread. Its treatment is the same as that of pulmonary TB, but the potential drug interactions between antiretroviral and anti-TB drugs in HIV-coinfected patients as well as the current recommended guidelines for the different types of anti-TB drugs resistance should be followed.
Keywords: pleural effusion; heart failure; tuberculous pleurisy; cirrhosis; portal hypertension; spontaneous bacterial empyema